Hardness of TiVN and TiN coating on AISI-316 stainless steel and HSS high speed steel - Figueroa, Robinson (2000)
We report here the production of TiN and TiVN hard coatings on stainless steel and high speed steel by the magnetron sputtering technique. The composite Vickers hardness, or hardness of the substrate plus coating system, was measured with the help of the Buehler Micromet 2101 micro-hardness tester. All the results obtained indicate a value of the composite hardness greater than that of the substrate. Following a model previously proposed by other authors, the contribution of the hardness of the coatings to the composite hardness has been determined. The thickness of the layers, over a period of 140 minutes, is on average 4.3 um. The hardness values ​​obtained range between 1100 and 2200 kg/mm2.